Monitoring a předpovídání populační početnosti hraboše polního - Tkadlec, E. (Emil); Heroldová, M. (Marta); Obdržálková, D.; Zejda, J.; Zapletal, M. (2010)
Although the monitoring of common vole (Microtus arvalis) populations in central Europe has been carried out for decades, quantitative forecasting models have rarely been implemented. Here we describe the population dynamics of the common vole in the Czech Republic over a period 2000-2009 and propose mathematical models for prediction of spring and autumn population densities at the level of districts. These models are based on functions for negative feedbacks, with the parameter estimates being obtained by model averaging. The forecasts made at the end of 2008 were in a good agreement with observations for most districts. For 2010, the models predict low numbers in most districts but the degree of uncertainty is still high. The results emphasize the importance of the monitoring programme and its regular execution as a basis for creating well-informed predictive management and successful plant protection against the common vole in the Czech Republic.